Аналіз працездатності тришарошкових бурових доліт типу ОК З відкритою опорою - Крижанівський, Є.І.; Яким, Р.С.; Шмандровський, Л.Є.; Петрина, Ю.Д. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
At is denoted the importance of rock bits using according to the optimum scheme of working out and concrete mining and geological conditions on the basis of efficiency analysis of three-cone rock bits with the opened bearing. Directions of the efficiency increase of bearings and bit cones rock destroyed equipment are determined.